The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1179/cim.2003.4.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Appreciation of music in adult patients with cochlear implants: a patient questionnaire

Abstract: Many cochlear implant candidates express hopes of enjoying music following implantation. Our aim was to assess the appreciation of music after cochlear implantation in adult patients. Thirty-five out of 45 cochlear implantees (78%) from the North East Programme responded to a questionnaire. Only 16 out of 35 patients (46%) listened to music after implantation. Enjoyment of music on a self-assessment scale was graded a mean of 8.7/10 before deafness but only 2.6/10 after implantation. Listening to music after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 7 publications
3
46
0
5
Order By: Relevance
“…Empirical assessments of music perception in adult CI users have found that while perception of rhythm approaches levels of accuracy comparable to NH population, perception of pitch is particularly impaired (McDermott 2004; Galvin, Fu, & Nogaki 2007; Gfeller et al 2007; Cooper et al 2008). Given the importance of pitch in music, it is not surprising that many adults using CIs report low levels of music appreciation after implantation (Mirza et al 2003; but see Fuller et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Empirical assessments of music perception in adult CI users have found that while perception of rhythm approaches levels of accuracy comparable to NH population, perception of pitch is particularly impaired (McDermott 2004; Galvin, Fu, & Nogaki 2007; Gfeller et al 2007; Cooper et al 2008). Given the importance of pitch in music, it is not surprising that many adults using CIs report low levels of music appreciation after implantation (Mirza et al 2003; but see Fuller et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Four to eight spectral channels may be adequate for speech understanding in optimal listening conditions, but complex listening tasks such as speech understanding in noise, talker identification, and music perception require more than 32 channels to maintain good performance (Friesen et al 2001; Smith et al, 2002; Shannon et al 2004; Vongphoe and Zeng, 2005). Current CI technology does not provide sufficient information for complex pitch perception, which makes music perception and appreciation difficult for CI users (Smith et al 2002; Mirza et al 2003; Shannon et al 2004; Vandali et al 2005; Looi et al 2012). CIs also do not provide voice pitch cues important for perception of vocal emotion (Xin et al 2007), speech prosody (Chatterjee and Peng 2008), and lexical tones (Peng et al 2004; Morton et al 2008; Han et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the 1990s already mentioned that CI users longed for pleasant music perception (3) . Others showed that less than one-third patients could perceive music with the CI (4,5) . The impact of music on the quality of life of CI users was investigated, and the authors observed that the levels of music appreciation were significantly lower after surgery when compared to the period before hearing loss (HL).…”
Section: Introductionmentioning
confidence: 99%